Chinese Strategic Decision-making on CSR - Wang, Shuo.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
This research study attempts to provide a comprehensive CSR literature review, analyze corporate social responsibility (CSR) issues from the strategic decision-making (SDM) perspective, and investigate the process of managers$1 (BCSR- related SDM in China. In particular, it utilizes content analysis to examine selected CSR articles from published studies, in order to evaluate the trends in CSR theory development as well as to identify the variables, constructs, and relationships within CSR theory. The review indicates that CSR should be involved in organizational strategies. Therefore, this study reviews the relevant theoretical and empirical literature in the SDM area. Firstly, it summarizes the broader context of strategic decisions and points out factors in the external environment and organizational characteristics that influence the SDM process of managers. Secondly, it articulates the influences of individual characteristics on the SDM. Thirdly, it examines the process of SDM using the rational and bounded rationality theory of decision making. Finally, on the basis of the SDM model, the author generates a research model which proposes the links between vital and influential factors from an integrated perspective. This book also provides a detailed description of how to choose a proper method for the CSR-related SDM research, the process of survey design, sampling methods, and survey administration. In particular, the author utilized a policy-capturing method to develop a series of scenarios concerning CSR activities and an explanation of this method is provided. It reports research findings of this study and provides an extensive and thorough discussion and compares it with previous empirical studies. The conclusion summarizes the research findings and their theoretical and practical implications.s
Introduction -- Literature review of corporate social responsibility -- CSR-related SDM process and hypothesis development -- Methodology and research design -- Data analysis and hypothesis testing -- Discussion of findings -- Conclusion.
Keywords: Economics; Industrial management; Marketing; Economics/Management Science; Business Strategy/Leadership.; Marketing; Management/Business for Professionals